How Resilient Are Military Expenditures in the Context of Fund-Supported Programs? - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper examines how military spending has been affected by Fund-supported programs. It looks at the changes in military expenditure as a share of gross domestic product (MIL/GDP) and of total expenditure (MIL/EX) for two subsamples of Fund-supported programs, broadly divided into fiscal tightening and fiscal accommodating. Under fiscal tightening, the evidence suggests that MIL/GDP decreases during Fund-supported programs, but that MIL/EX increases, revealing resilience to budgetary adjustments. Under fiscal accommodation, as total government expenditure tends to increase, so does military expenditure; however, the ratio MIL/EX declines, as fewer additional resources are allocated to the military.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet